Suicide intervention training for college staff: Program evaluation and intervention skill measurement. Issue 7 (3rd October 2017) - Shannonhouse, Laura; Lin, Yung-Wei Dennis; Shaw, Kelly; Wanna, Reema; Porter, Michael
ABSTRACT: Objective : Suicide remains a pressing issue for college communities. Consequently, gatekeeper trainings are often provided for staff. This study examines the effect of one such program, Applied Suicide Intervention Skills Training (ASIST).Participants : 51 college employees received ASIST in August of 2014 and were compared to 30 wait-list control participants.Methods : Repeated Measures ANOVA were used to analyze pre- and post-training: (a) skills at responding to students-at-risk; (b) attitudes toward suicide; (c) knowledge about suicide; and (d) comfort/competence/confidence at helping a student-at-risk.Results : Significant positive training effects were observed for ASIST on self-report measures and also for objectively assessed skill at responding, after adjusting for a potential scoring limitation of the Suicide Intervention Response Inventory, Revised (SIRI-2).Conclusions : ASIST improved the self-perception of college staff at working with students-at-risk of suicide and also their skills at performing an intervention. Further, analysis of SIRI-2 data provides support for a potential instrument revision.